1999
DOI: 10.1037/1076-8998.4.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Method for retrospective collection of work-related psychosocial risk factors for musculoskeletal disorders: Reliability and aggregation.

Abstract: Information on psychosocial work conditions during a 24-year period for 484 participants was collected retrospectively. Analyses were made of the interrater reliability, stability, specificity, and aggregation of data. The main finding was that it is possible to collect reliable information about psychosocial work conditions retrospectively for a long period of years when using a time ruler in a structured interview when earlier conditions are compared with the present. Interrater agreement was satisfactory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The questions on intensity and frequency of pain extended over a period of 3 months. Recall bias may have been present; however, with reference to previous studies on selfreported data, the validity can be considered acceptable (Bildt Thorbjörnsson et al 1999;Fredriksson et al 1998;Torgén et al 1999). This is a cross-sectional study.…”
Section: Methodological Considerationsmentioning
confidence: 91%
“…The questions on intensity and frequency of pain extended over a period of 3 months. Recall bias may have been present; however, with reference to previous studies on selfreported data, the validity can be considered acceptable (Bildt Thorbjörnsson et al 1999;Fredriksson et al 1998;Torgén et al 1999). This is a cross-sectional study.…”
Section: Methodological Considerationsmentioning
confidence: 91%
“…It is also assumed that recent events are more easily recalled. However, there are studies that have shown good agreement between recalled events and official records (Baumgarten et al 1983, Martin 1987, Stewart et al 1987, Theorell et al 1999, Torbjö rnsson et al 1999). Nilsen (1992 and Ringsberg et al (2001) have used, and endorse, a technique that focuses on the reporting of important life events.…”
Section: Discussionmentioning
confidence: 99%
“…Although retrospective recall is a valid method to study emotion-laden events (Salovey, Sieber, Jobe, & Willis, 1994;Thorbjörnsson, Michelsen, & Kilbom, 1999), methods that assess the test-takers' experiences in real-time (such as experience sampling) would be useful to understand immediate test reactions. Indeed, real-time assessments have been used to understand other aspects of the test anxiety nomological net, such as the association between test anxiety, coping strategies and negative affect (Stowell, Tumminaro & Attarwala, 2008).…”
Section: Limitations and Future Researchmentioning
confidence: 99%